Principles of sustainable energy systems - 9; Kreith, Frank (Boca Raton, Florida : CRC Press, 2013)
"This is an ideal book for seniors and graduate students interested in learning about the sustainable energy field and its penetration. The authors provide very strong discussion on cost-benefit analysis and ROI calculations for various alternate energy systems in current use. This is a descriptive book with detailed case-based analyses of various systems and engineering applications. The text book provides real-world case studies and related problems pertaining to sustainable energy systems.""--Dr. Kuruvilla John, University of North Texas""The new edition of ""Principles of Sustainable En.
Front Cover; Dedication; Contents; Foreword; Preface; Acknowledgments; Contributors; Chapter 1. Introduction to Sustainable Energy; Chapter 2. Economics of Energy Generation and Conservation Systems; Chapter 3. Wind Energy; Chapter 4. Capturing Solar Energy through Biomass; Chapter 5. Fundamentals of Solar Radiation; Chapter 6. Photovoltaics; Chapter 7. Solar Heating and Cooling of Buildings; Chapter 8. Solar Process Heat and Thermal Power; Chapter 9. Passive Solar Heating, Cooling, and Daylighting; Chapter 10. Energy Storage; Chapter 11. Ocean Energy Conversion; Chapter 12. Transportation.
Revised edition of: Principles of sustainable energy / Frank Kreith, Jan F. Kreider. 2011.
Includes bibliographical references and index.
Keywords: Renewable energy sources